2020
DOI: 10.1002/epi4.12432
|View full text |Cite
|
Sign up to set email alerts
|

Availability, affordability, and quality of essential antiepileptic drugs in Lao PDR

Abstract: Objective Epilepsy is a chronic condition treatable by cost‐effective antiepileptic drugs (AEDs), but limited access to treatment was documented. The availability and affordability of good quality of AEDs play a significant role in access to good health care. This study aimed to assess the availability, affordability, and quality of long‐term AEDs in Lao PDR. Method A cross‐sectional study was performed in both public and private drug supply chains in urban and rural areas in Lao PDR. Data on AEDs availability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 33 publications
1
15
1
Order By: Relevance
“…The availability found in our study was lower than previous studies in other border countries such as Vietnam (>36.0% for carbamazepine and phenytoin) 36 and Thailand (above 80%) 37, 38 . In contrast, we found a higher availability and better affordability than a recent study in Lao PDR, conducted over the same period with the same methodology, and reported availability of less than 15.0% 8 . This difference could be partly explained by the type of facilities considered.…”
Section: Discussioncontrasting
confidence: 96%
See 4 more Smart Citations
“…The availability found in our study was lower than previous studies in other border countries such as Vietnam (>36.0% for carbamazepine and phenytoin) 36 and Thailand (above 80%) 37, 38 . In contrast, we found a higher availability and better affordability than a recent study in Lao PDR, conducted over the same period with the same methodology, and reported availability of less than 15.0% 8 . This difference could be partly explained by the type of facilities considered.…”
Section: Discussioncontrasting
confidence: 96%
“…For data collection, availability and affordability endpoints, and data analysis were adapted from those used in another project performed in Lao PDR and published in 2020 8 …”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations